Nitrogen doped graphene with diamond-like bonds achieves unprecedented energy density at high power in a symmetric sustainable supercapacitor. Issue 2 (7th January 2022) - Šedajová, Veronika; Bakandritsos, Aristides; Błoński, Piotr; Medveď, Miroslav; Langer, Rostislav; Zaoralová, Dagmar; Ugolotti, Juri; Dzíbelová, Jana; Jakubec, Petr; Kupka, Vojtěch; Otyepka, Michal
Abstract : A nitrogen-superdoped graphene with diamond-like interlayer bonds is obtained via the radical chemistry of fluorographene, affording a symmetric supercapacitor with an energy density of 200 W h L −1 at a power of 2.6 kW L −1 and 143 W h L −1 at 52 kW L −1 . Abstract : Supercapacitors have attracted great interest because of their fast, reversible operation and sustainability. However, their energy densities remain lower than those of batteries. In the last decade, supercapacitors with an energy content of ∼110 W h L −1 at a power of ∼1 kW L −1 were developed by leveraging the open framework structure of graphene-related architectures. Here, we report that the reaction of fluorographene with azide anions enables the preparation of a material combining graphene-type sp 2 layers with tetrahedral carbon–carbon bonds and nitrogen (pyridinic and pyrrolic) superdoping (16%). Theoretical investigations showed that the C–C bonds develop between carbon-centered radicals, which emerge in the vicinity of the nitrogen dopants. This material, with diamond-like bonds and an ultra-high mass density of 2.8 g cm −3, is an excellent host for the ions, delivering unprecedented energy densities of 200 W h L −1 at a power of 2.6 kW L −1 and 143 W h L −1 at 52 kW L −1 . These findings open a route to materials whose properties may enable a transformative improvement in the performance of supercapacitor components.